Synthesis of some novel Heterocyclic Chalcone Derivatives - Hassan Shntaif, Ahmed (Al-Qadisiyah Journal of Pure Science, 2018)
The derivatives of Chalcones were synthesized by reaction of 2,3-Dichlorobenzaldehyde with 2-Hydroxy acetophenone in the base medium, then the product react with thiourea, urea and hydrazine to preper the derivatives of thiazine, oxazine and isoxazole respectively. The structures of the synthesized compounds have been characterized by (IR, 1HNMR, 13CNMR and elemental analysis). Keywords: Chalcone, Urea, Claisen-Schmidt condensation, Oxazine and Isoxazole.